Rapid method for identification of transgenic fish zygosity - . Alimuddin; G. Yoshizaki; O. Carman (Jurnal Akuakultur Indonesia)
Identification of zygosity in transgenik fish is normally achieved by PCR analysis with genomic DNA template extracted from the tissue of progenies which are derived by mating the transgenic fish and wild-type counterpart.  This method needs relatively large amounts of fish material and is time- and labor-intensive. New approaches addressing this problem could be of great help for fish biotechnologists.  In this experiment, we applied a quantitative real-time PCR (qr-PCR) method to analyze zygosity in a stable line of transgenic zebrafish (Danio rerio) carrying masu salmon, Oncorhynchus masou D6-desaturase-like gene. The qr-PCR was performed using iQ SYBR Green Supermix in the iCycler iQ Real-time PCR Detection System (Bio-Rad Laboratories, USA).  Data were analyzed using the comparative cycle threshold method.  The results demonstrated a clear-cut identification of all transgenic fish (n=20) classified as a homozygous or heterozygous.  Mating of those fish with wild-type had revealed transgene transmission to the offspring following expected Mendelian laws. Thus, we found that the qTR-PCR to be effective for a rapid and precise determination of zygosity in transgenic fish. This technique could be useful in the establishment of breeding programs for mass transgenic fish production and in experiments in which zygosity effect could have a functional impact.